Diagnóstico de estrés térmico de un ambiente laboral mediante el diseño y construcción de un medidor del índice TGBH – HR - Sánchez Ocaña, Wilson Edmundo (2013)
With the Industrial Revolution, risks have appeared derived from the daily activities carried out by people, which, if not controlled, lead to occupational diseases that in the long run affect the optimal development of a worker. Industrial works are carried out in closed, semi-closed and open places, where climatic conditions are generated that, although influenced by the external climate, normally differ from it. Workers in the wood, metallurgical, floriculture, artisanal, etc. industries are exposed to an aggressive thermal environment that can cause damage to their health, making it necessary to quantify exposure to high temperatures; this assessment is done through the temperature index. Thermal Stress (TGBH-WBGT).